2022
DOI: 10.1007/s10784-022-09569-4
|View full text |Cite
|
Sign up to set email alerts
|

Institutional interplay in global environmental governance: lessons learned and future research

Abstract: Over the past decades, the growing proliferation of international institutions governing the global environment has impelled institutional interplay as a result of functional and normative overlap across multiple regimes. This article synthesizes primary contributions made in research on institutional interplay over the past twenty years, with particular focus on publications with International Environmental Agreements: Politics, Law and Economics. Broadening our understanding about the different types, dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Based on the topic analysis results and the context from the Nationally Determined Contributions and Long-Term Strategies documents, there is clearly a lack of integration and alignment of climate objectives and actions by non-state actors with those by the national governments. These results confirm the observations of Elsässer et al (2022), which also found increasing fragmentation and complexities in global environmental governance despite growing interactions among transnationally operating institutions. The repeatedly stated need for identifying, consolidating, and aligning institutional arrangements and ministries suggests a persisting lack of national and international guidance, coordination and governance.…”
Section: Missing Non-state Actor and National Coordinationsupporting
confidence: 89%
“…Based on the topic analysis results and the context from the Nationally Determined Contributions and Long-Term Strategies documents, there is clearly a lack of integration and alignment of climate objectives and actions by non-state actors with those by the national governments. These results confirm the observations of Elsässer et al (2022), which also found increasing fragmentation and complexities in global environmental governance despite growing interactions among transnationally operating institutions. The repeatedly stated need for identifying, consolidating, and aligning institutional arrangements and ministries suggests a persisting lack of national and international guidance, coordination and governance.…”
Section: Missing Non-state Actor and National Coordinationsupporting
confidence: 89%
“…This observation highlights that most high-emitting jurisdictions have sets of policies aiming to mitigate climate change. Thus, scholars contend that policies exist and operate as part of a policy-mix or policyscape (Wurzel et al, 2019;Therville et al, 2020;Zabala, 2021;Elsässer et al, 2022). This argument reflects both theoretical and empirical observations.…”
Section: Setting the Scene: Climate Policyscapesmentioning
confidence: 93%
“…These frameworks not only shape the conduct of states and non-state actors but also define the contours of cooperation and conflict resolution in the environmental domain. Drawing upon the insights provided by Yu (2022), Scicluna (2021), andElsässer et al (2022), this analysis explores the pivotal role of international law and policy frameworks in steering global environmental governance, highlighting their effectiveness, challenges, and the dynamics of institutional interplay. Yu (2022) delves into the effectiveness of international law in global environmental relations, employing the lens of international institutional theory.…”
Section: The Role Of International Law and Policy Frameworkmentioning
confidence: 99%